2009
DOI: 10.2174/092986709789578187
|View full text |Cite
|
Sign up to set email alerts
|

The Structure and Pharmacological Functions of Coumarins and Their Derivatives

Abstract: Coumarins are of many different structures. They constitute an important class of pharmacological agents possessing a range of different physiological activities including anti-cancer, anti-oxidant, anti- inflammation, anti-HIV, anti-coagulant, anti-bacterial, analgesic and comparative immune-modulation. Recently, coumarins have attracted intense research interest. Of great interest is the possibility that this class of molecules could be a source of drugs for the therapy of several diseases. These include rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
138
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(141 citation statements)
references
References 150 publications
(256 reference statements)
0
138
0
3
Order By: Relevance
“…Previously we found that the plant coumarin oreoselone (14) by reaction with p-toluenesulfonyl chloride gave 2-(tosyl)oreoselone (15), which showed a high activity in Pd-catalyzed desulfonative cross-coupling reactions [19]. Herein, oreoselone (14) was converted into 2-(arylethynyl)furocoumarins 16-20 by the copper-free cross-coupling reaction with arylalkynes 21a-e in the presence of p-toluenesulfonyl chloride. After the purification by column chromatography compounds 16-20 were isolated in 44%-62% yield.…”
Section: Chemical Synthesismentioning
confidence: 97%
See 2 more Smart Citations
“…Previously we found that the plant coumarin oreoselone (14) by reaction with p-toluenesulfonyl chloride gave 2-(tosyl)oreoselone (15), which showed a high activity in Pd-catalyzed desulfonative cross-coupling reactions [19]. Herein, oreoselone (14) was converted into 2-(arylethynyl)furocoumarins 16-20 by the copper-free cross-coupling reaction with arylalkynes 21a-e in the presence of p-toluenesulfonyl chloride. After the purification by column chromatography compounds 16-20 were isolated in 44%-62% yield.…”
Section: Chemical Synthesismentioning
confidence: 97%
“…The cytotoxic activity of the synthesized series of 2-(Z)-styryldihydrofurocoumarins 2,3,6-8, 3-(Z)-styrylfurocoumarins 4,5,9-13, the parent oreoselone (14) and combretastatin A-4 (1) was determined by measuring the concentration inhibiting human tumor cell viability by 50% (CTD 50 ). The CTD 50 was determined using the conventional MTT assay, which allows to estimate the number of survived cells spectrophotometrically [27].…”
Section: Cytotoxicity Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…These compounds have the ability to engage in non-covalent interactions (hydrophobic, π-π, and electrostatic interactions as well hydrogen bonding, metal coordination, van der waals forces etc.) with various active sites in bimolecules, and thus display a wide range of biological activities, such as anticoagulant [13], antineurodegenerative [14], antioxidant [15], anticancer [16], anti-inflammatory, anti-diabetes, antidepresive [15], antimicrobial efficacies [17], etc. 4-hydroxycoumarin derivatives of natural or synthetic origin has attracted much interest in several fields [18]- [20].…”
Section: Coumarin and Biscoumarinmentioning
confidence: 99%
“…9 Coumarins belonging to different chemical classes have been studied. 10 There are evidences of the antiretroviral activity of coumarin derivatives and their ability to inhibit HIV integrase.…”
Section: Introductionmentioning
confidence: 99%